Expanding the clinical and phenotypic heterogeneity associated with biallelic variants in ACO2. Issue 6 (9th June 2020) - Blackburn, Patrick R.; Schultz, Matthew J.; Lahner, Carrie A.; Li, Dong; Bhoj, Elizabeth; Fisher, Laura J.; Renaud, Deborah L.; Kenney, Amy; Ibrahim, Niema; Hashem, Mais; Zain Seidahmed, Mohammed; Hasadsri, Linda; et al.
Abstract: Objective: We describe the clinical characteristics and genetic etiology of several new cases within the ACO2‐related disease spectrum. Mitochondrial aconitase (ACO2) is a nuclear‐encoded tricarboxylic acid cycle enzyme. Homozygous pathogenic missense variants in the ACO2 gene were initially associated with infantile degeneration of the cerebrum, cerebellum, and retina, resulting in profound intellectual and developmental disability and early death. Subsequent studies have identified a range of homozygous and compound heterozygous pathogenic missense, nonsense, frameshift, and splice‐site ACO2 variants in patients with a spectrum of clinical manifestations and disease severities. Methods: We describe a cohort of five novel patients with biallelic pathogenic variants in ACO2 . We review the clinical histories of these patients as well as the molecular and functional characterization of the associated ACO2 variants and compare with those described previously in the literature. Results: Two siblings with relatively mild symptoms presented with episodic ataxia, mild developmental delays, severe dysarthria, and behavioral abnormalities including hyperactivity and depressive symptoms with generalized anxiety. One patient presented with the classic form with cerebellar hypoplasia, ataxia, seizures, optic atrophy, and retinitis pigmentosa. Another unrelated patient presented with ataxia but developed severe progressive spastic quadriplegia. Another patient demonstrated a spinal muscular atrophy‐like presentation with severe neonatal hypotonia, diminished reflexes, and poor respiratory drive, leading to ventilator dependence until death at the age of 9 months. Interpretation: In this study, we highlight the importance of recognizing milder forms of the disorder, which may escape detection due to atypical disease presentation.